Analysis of Fe3O4 thin film electrical properties prepared from iron sand at Tiram Beach, Padang Pariaman Regency, West Sumatra by using the sol-gel spin coating method - Fitria Murti; Ramli Ramli; Yenni Darvina (PILLAR OF PHYSICS, 2017)
Indonesia is a country that has a considerable amount of mining products such as iron sand that can be found along the beach, one of them is the Tiram Beach in Padang Pariaman district, West Sumatera. Iron sand can be applied to electronics, computing, and the automotive industry sector because it contains magnetic material. Magnetite iron sand is iron oxidation which has the strongest magnetic characteristic, which is made in nano size has ferromagnetic characteristic and has a wide application, the development of ferrite materials in the form of thin layer oriented to recording media and also can be used as a magnetic sensor device. The research is to inquire effect  spin coating velocity on conductivity of thin layer.In the research, variation of spin coating velocity 1000 rpm, 2000 rpm, and 3000 rpm are done with the time of 60 seconds toward magnetite gel solution which has been sol-gel, after rotated then the thin layer formed is measured by using four point probe method. The result from research obtained conductivity value that is on velocity 1000 , 2000, and 3000 rpm conductivity value shows that the effect of spin coating velocity on the magnetite thin layer conductivity that is the higher it is spin coating speed, the higher it is the conductivity